Menyelami proses siklus hidrologi dalam pengelolaan Sumber Daya Air: Pentingnya bagi kehidupan - Ikrimah, Lailatul (Maliki Interdisciplinary Journal, 2024)
The water cycle is a natural process that reuses water on earth through stages such as evaporation, condensation, precipitation, percolation and surface runoff. This process is critical in water resources management, because understanding the dynamics of the water cycle allows planning and implementing effective water conservation and distribution strategies. Hydrology, the science that studies this cycle, plays an important role in many aspects of human life, from providing clean water, agricultural irrigation, to mitigating natural disasters such as floods and droughts. This article explores the importance of hydrology in supporting everyday life and how knowledge about water cycle processes can be used for sustainable water resource management. When addressing the challenges of climate change, a hydrological approach is essential to develop adaptive solutions that ensure the sustainability and continuity of ecosystems and human water needs. Integrating the latest technology can improve water resource management and increase water security and community welfare.